2011
DOI: 10.1517/14656566.2011.634801
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of neurocysticercosis

Abstract: Anticysticercal therapy has been marked by intense controversy. Recent descriptions of spontaneous resolution of parenchymal cysticercosis with benign evolution, risks of complications and reports of no long-term benefits have reinforced the debate over the usefulness and safety of anticysticercal therapy. High interindividual variability and complex pharmacological interactions will require the close monitoring of plasma concentrations of ALB and PZQ metabolites in future trials. Given the relative scarcity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…A pilot study for such an integrated control strategy for schistosomiasis has been undertaken in China using a multi-pronged approach, including health education, access to clean water and adequate sanitation, mechanisation of agriculture, and fencing of water buffaloes, along with chemotherapy [56][58]. In the case of cestode infections, and despite the proven benefit of chemotherapy with praziquantel and possibly albendazole for patients with parenchymal NCC [59], [60], there is a need for improved drugs and/or studies with drug combination regimens and dosages to evaluate their efficacy [61].…”
Section: Advances Opportunities and Challenges For The Control And mentioning
confidence: 99%
“…A pilot study for such an integrated control strategy for schistosomiasis has been undertaken in China using a multi-pronged approach, including health education, access to clean water and adequate sanitation, mechanisation of agriculture, and fencing of water buffaloes, along with chemotherapy [56][58]. In the case of cestode infections, and despite the proven benefit of chemotherapy with praziquantel and possibly albendazole for patients with parenchymal NCC [59], [60], there is a need for improved drugs and/or studies with drug combination regimens and dosages to evaluate their efficacy [61].…”
Section: Advances Opportunities and Challenges For The Control And mentioning
confidence: 99%
“…Alternatively, a 15-day treatment with a daily dose of 50 mg/kg praziquantel in 3 divided doses was also effective for treatment of parenchymal brain cysticercosis [55]. However, several studies have reported better results with replacement of praziquantel with albendazole (7-day course) or a combination of albendazole and praziquantel for treatment of subarachnoid and ventricular cysticercosis [56, 57]. In the treatment of cerebral cysticercosis, administration of corticosteroids such as dexamethasone should accompany the anthelmintic treatment in order to reduce adverse reactions such as headache, vomiting, and neurological symptoms which can occur due to elevated incracranial pressure resulting from inflammatory reactions against antigens liberated from dying cysticerci worms [2].…”
Section: Recommended Dose and Efficacymentioning
confidence: 99%
“…Treatment : Albendazole and praziquantel are the mainstay drugs for treatment of NCC, especially for meningeal infection and steroids should be administered to reduce oedema as a result of medical treatment58.…”
Section: Diseases Due To Tissue Parasites In Hiv/aids Patientsmentioning
confidence: 99%